Perencanaan Alternatif Dinding Penahan Badan Jalan (Kantilever) Pada Ruas Jalan Pulau Haruku - Dahoklory, Hendrik; Hutubessy, Vector R. R.; Matitaputty, Apri Adam (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The construction of a retaining wall at this location was due to landslides caused by high rainfall in the area. The purpose of this planning is to determine the characteristics of the soil at the research location and determine the stability of the road retaining wall designed using a cantilever on the stability of rolling forces, shear forces and soil bearing capacity. The method used is the Terzaghi method as a planning reference. Then the results of the stability analysis of the road body retaining walls are, shifting stability with a value of 1,444 <1.5, stability against overturning 2,632 > 1.5 and bearing capacity stability 10,132 > 3.